Numerical and Experimental Analysis of Wood Tensile Strength Perpendicular to the Grain - Silva, Joäo Vítor Felippe [UNESP]; de Araujo, Patrik Luiz Silva [UNESP]; de Oliveira, Karina Aparecida [UNESP]; Silva, Maria Fernanda Felippe [UNESP]; Oliveira, Carolina Aparecida [UNESP]; Molina, Julio Cesar [UNESP] (FapUNIFESP (SciELO), 2022)
The Brazilian Code ABNT NBR 7190 (1997) is currently under review process and one of the proposals is the change and add of some test procedures. Several specimen geometric configurations and test conditions have been evaluated by the study committee CE-02:126.10. The aim of this paper was the analysis of the tensile strength perpendicular to the grain through the current Brazilian Code and from an adaptation of ISO 13910 (2005). Pine and Indian Cedar were used and simplified relationships were proposed. Numerical simulations were performed to identify the stress distributions in the specimens. The results obtained by ISO 13910 (2005) did not differ statistically for the two species. Brazilian standard method cedar had a higher strength value than pine. The simplified ratios obtained ranged between 0,017 and 0,123. The numerical simulations of ISO 13910 (2005) specimens showed predominant failure by tension in the lower fiber due to stress concentration.
Keywords: Finite Element Method; Mechanical Testing; Standardization; Wood Strength